If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -3b = -12 Solving 2a + -3b = -12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3b' to each side of the equation. 2a + -3b + 3b = -12 + 3b Combine like terms: -3b + 3b = 0 2a + 0 = -12 + 3b 2a = -12 + 3b Divide each side by '2'. a = -6 + 1.5b Simplifying a = -6 + 1.5b
| 36x^2+2x+7=0 | | 5+s+3+4= | | 24-12x=6x-30 | | 5x^3-15x^2+x-3= | | 9=5+2d | | 4t=153t | | 4m-2=2m | | 4x-25+2x+5=x | | -.4d=-6.4 | | 1.7p-3=0.9+13 | | 3b-4b=4 | | 7-4=6x+11 | | 8+4x=5x+5 | | -3y-19+5y=-22 | | 4x-6x-16=-2x+3-16 | | 7x+2=5x+15 | | .25x-8+.5x=19 | | 10-2x=3(x+4)-2 | | 10h=-.1 | | 9=2j+1 | | 9=1+2b | | 3x+2(x+2)=5x+4 | | -2.5s=25 | | 2x+2+7x=-6x-2x | | .4x-8+.5x=19 | | 2(x+1)=3(x+4) | | 4+2i=4 | | 12y=1x+b | | -8g=.48 | | 0.6r=.0005 | | -7y=-6.3 | | 2(x+1)=3(x+4)+10 |